ANGGARAN KINERJA MELALUI PENDEKATAN VALUE FOR MONEY DI KABUPATEN BONE BOLANGO - Afni, Meyke Nur; Abdullah, Julie; Junus, Onong; Saprudin, Saprudin; Masjhur, Mohamad Abdul Radjak (KINDAI, 2025)
Implementing government financial management involves periodic evaluation of the implementation of the financial management system. One way of organizing the state and managing government finances is by using the concept of value for money. Value for money, often called economics, efficiency, and effectiveness, can be used to evaluate local government performance through performance-based budgeting. The data collection technique in this study is documentation by collecting data using the Budget Realization Report (LRA) 2018-2023. The analysis technique used is the economic, efficiency, and effective ratio formula. The results showed that from 2018 to 2021, the financial performance of the Bone Bolango Regency Government was said to be economical, the efficiency ratio of the financial performance of the Bone Bolango Regency Government from 2018 to 2023 was declared less efficient, and in 2018-2023, it was said to be effective. Keywords: performance based budget, financial performance, value for money